Development of automotive basics learning module Sub-Subject Special Service Tools (SST) based on augmented reality - I Gede Diva Sumarta Yana; Kadek Rihendra Dantes; Edi Elisa (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
Based on preliminary research conducted in the Automotive Engineering class of SMK Negeri 3 Singaraja, it was found that the obstacles faced by students in the learning process were 90% of the 30 students stating that they did not have modules or other handbooks to learn the Special Service Tools (SST) sub-material. 73.3% stated that it was difficult to understand the material through teaching materials and methods applied by the teacher, so that students had difficulty in understanding how to use the types of Special Service Tools (SST) according to their functions. 90% of students stated that they were very happy and interesting if the learning activities of the Special Service Tools (SST) sub-material were presented using learning media that varied with audio, visual, audio-visual media. This research produced learning media in the form of Augmented Reality-based modules that can be accessed individually with a smartphone device to display 3-dimensional objects of the Special Service Tools (SST) type and how to use them. The research method used is research and development using the ADDIE model which consists of analysis, design, development, implementation, evaluation. The results of this study show that the learning module automotive basics sub subject Special Service Tools (SST) based on augmented reality is stated to be very feasible and very practical to use. The percentage of material experts, media experts, small and large group trials are 93%, 87.89%, 88.55% and 90.83% which are categorized as very feasible and very practical.